Health-related quality of life among undergraduate dentistry students in Ho Chi Minh, Vietnam: A cross-sectional WHOQOL‑BREF study. - Trung Quang Vo; Duy Duc Tran; Hien Thi Thuong Dinh (GarVal Editorial Ltda., 2020)
Context: Dentistry is one of the most stressful and difficult programs in Vietnam. The quality of life (QoL) of dentistry students strongly affects their learning ability and is an issue that causes anxiety among educators. Aims: To assess the QoL of dentistry students using the World Health Organization Quality of Life Instrument - Short Form (WHOQOL-BREF) and to explore the relationship between questionnaire scores and participant characteristics. Methods: A cross-sectional survey was administered directly in February to May 2019 with the participation of 201 dentistry students from three universities in southern Vietnam. Results: The mean scores of the students in the four WHOQOL-BREF domains were 57.20 ± 11.93 (physical health), 53.75 ± 14.78 (psychological health), 59.70 ± 15.68 (social relationships), and 55.79 ± 13.25 (environment). Their QoL scores were lower than those of their counterparts in the US and Pakistan. The female students had lower psychological, environmental, and physical health domain scores than those acquired by the male students (p<0.01). The frequency of physical exercise and average sleep duration was significantly associated with all the QoL domains (p<0.05). Conclusions: The WHOQOL-BREF is a suitable questionnaire for evaluating the QoL of Vietnamese dentistry students. To improve the health and well-being of this population, medical universities should innovate dentistry education programs and provide essential support, especially to female and fourth year students. Such institutions should also encourage students to participate in sport activities outside learning time and obtain enough sleep for a healthy body and satisfactory academic performance.